A NEW WORLD WAR IN K-POP: RED VS BLUE - , ANITA MARET PRASETYOWATI, Ms Erlin Estiana Yuanti, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper aims to discover the new and interesting habit coming from K-Pop fans, especially fans of TVXQ and Super Junior which is called fanwar. It identifies and describes about fanwar between Cassiopeia and Elf in detail, starting from the places of fanwar, reasons of fanwar, and positive aspects to learn from fanwar and fangirl. Furthermore, this paper is expected to give information about K-Pop world for people who are not familiar with it. The methods of collecting the data are conducted by doing the observation, giving questionnaire, and library research. The observation has been conducted since 2012 in order to know the phenomenon of fanwar well. The questionnaires were distributed on March 2013 to 50 fangirls from both fandoms in order to get the data and information about the fanwar between Cassiopeia and Elf. Meanwhile, the library research was done to collect some additional information to support the discussion in this paper. Based on the observation, fanwar between Cassiopeia and Elf happens on social networks such as Facebook, Twitter, Youtube, and personal blog. The fanwar happens because of three main reasons